Enhanced neuronal survival and BDNF elevation via long-term co-activation of galanin 2 (GALR2) and neuropeptide Y1 receptors (NPY1R): potential therapeutic targets for major depressive disorder - Borroto Escuela, Dasiel Óscar; Serrano-Castro, Pedro Jesús; Sánchez-Pérez, José Andrés; Barbancho-Fernández, Miguel Ángel; Fuxe, Kjell; Narváez-Peláez, Manuel (Taylor & Francis, 2024)
Background: Major Depressive Disorder (MDD) is a prevalent and debilitating condition, necessitating novel therapeutic strategies due to the limited efficacy and adverse effects of current treatments. We explored how galanin receptor 2 (GALR2) and Neuropeptide Y1 Receptor (NPYY1R) agonists, working together, can boost brain cell growth and increase antidepressant-like effects in rats. This suggests new ways to treat Major Depressive Disorder (MDD). Research Design and Methods: In a controlled laboratory setting, adult naive Sprague-Dawley rats were administered directly into the brain’s ventricles, a method known as intracerebroventricular (ICV) administration, with GALR2 agonist (M1145), NPYY1R agonist, both, or in combination with a GALR2 antagonist (M871). Main outcome measures included long-term neuronal survival, differentiation, and behavioral. Results: Co-administration of M1145 and NPYY1R agonist significantly enhanced neuronal survival and maturation in the ventral dentate gyrus, with a notable increase in Brain-Derived Neurotrophic Factor (BDNF) expression. This neurogenic effect was associated with an antidepressant-like effect, an outcome partially reversed by M871. Conclusions: GALR2 and NPYY1R agonists jointly promote hippocampal neurogenesis and exert antidepressant-like effects in rats without adverse outcomes, highlighting their therapeutic potential for MDD. The study’s reliance on an animal model and intracerebroventricular delivery warrants further clinical exploration to confirm these promising results.
Keywords: Neuropéptidos; Antidepresivos; Neurobiología del desarrollo; Antidepressant effects; Galanin receptor 2 (GALR2) agonist; Major depressive disorder (MDD); Neuropeptide Y1 receptor (NPYY1R) agonist; Neurogenesis; Rodent model